Isotope and water chemistry data from tapwater and its sources in Addis Ababa, Ethiopia - Kebede, S; Hailu, K; Siraj, A; Birhanu, B (University of Oxford, 2024)
This data was collected as part of a study into the use of environmental tracers (Water isotopes-δ18O–δ2H, Radon-222Rn, and Electrical Conductivity-EC) as tools for backtracking to the water source, estimating pipe water residence time, and monitoring the instability of the water quality in piped water supplies in Addis Ababa, Ethiopia. For more details consult the paper: Environmental isotopes (δ18O–δ2H, 222Rn) and electrical conductivity in backtracking sources of urban pipe water, monitoring the stability of water quality and estimating pipe water residence time (https://doi.org/10.3389/frwa.2023.1066055).